Doppler auxiliary time synchronization algorithm for underwater acoustic sensor network - Xiao-ning FENG; Zhuo WANG; Xiao-long ZHU; Wen ZHANG (Tongxin xuebao)
Time synchronization problem in underwater acoustic sensor networks (UWSN) was studied.Due to the propagation of acoustic signals in underwater environment and nodes movement bring some problems to time synchronization.A distributed time synchronization algorithm was proposed based on Doppler method,called NU-Sync.NU-Sync solved the problem of uncertainty propagation delay caused by nodes movement through calculating relative velocity.And autonomous underwater vehicle (AUV) was used as beacon node which can save energy consumption in the process of calculation clock skew.Simulation resulted show NU-Sync achieves high level time synchronization precision.